I am stuck on this problem.
-[-|-3|(-2-m)-4] = -2[(-3-m)-2m]
I am an old duffer trying to learn some math.
Any help would be appreciated.
The answer is supposed to be -8/9
You have to work from the inside out on the parentesis then brackets
I started off with the absolute value sign and the steps are as follows:
-[-(3)(-2-m)-4]=-2[-3-3m] Absolute value of -3 and subtract -2m
-[6+3m-4]=6+6m Distribute -3 through and distribute -2 through
-[2+3m]=6+6m Add like terms together
-2-3m=6+6m Distribute the negative through the equation
-8=9m Put like terms on each side of the equation
-8/9=m Divide -8 by 9 to get your result
Hope this helps you!!